Molecular Electronics - Zotti, Linda Angela (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
This is a Special Issue on Molecular Electronics which provides an overview of the field and will be useful for both theoreticians and experimentalists. Topics include protein-based electronics, field-induced trans-to-cis isomerisation, phonon thermal conductance, spin-dependent transport, attenuation factors, HOMO-LUMO gap corrections and nanofabrication techniques.